2022
DOI: 10.3390/audiolres12060065
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Audiovestibular Symptoms between Early and Late Variants of COVID-19

Abstract: Audiovestibular symptoms during the acute phase of the corona virus disease 2019 (COVID-19), have been reported for earlier waves of the pandemic, while no studies investigated nor compared audiovestibular manifestations during subsequent waves of COVID-19. In the current study, we aimed to compare the occurrence of audiovestibular symptoms associated with COVID-19 between the alpha/beta, delta, and omicron variants. An online questionnaire was distributed to individuals with confirmed test results for COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
3
1
1
Order By: Relevance
“…The data we present demonstrate that individuals testing positive for COVID-19 are over twice as likely to develop vestibular symptoms compared to the general population. Although our data estimates the overall prevalence of vestibular disorder amongst these patients at between 1% and 3%, other studies have estimated the self-reported numbers to reach as high as over 40% ( 7 , 14 , 15 ). One must also consider individuals whose vestibular symptoms remain undiagnosed, those who did not seek medical attention for their vestibular symptoms during our observation window, and those who were never tested and diagnosed with COVID-19.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The data we present demonstrate that individuals testing positive for COVID-19 are over twice as likely to develop vestibular symptoms compared to the general population. Although our data estimates the overall prevalence of vestibular disorder amongst these patients at between 1% and 3%, other studies have estimated the self-reported numbers to reach as high as over 40% ( 7 , 14 , 15 ). One must also consider individuals whose vestibular symptoms remain undiagnosed, those who did not seek medical attention for their vestibular symptoms during our observation window, and those who were never tested and diagnosed with COVID-19.…”
Section: Discussioncontrasting
confidence: 77%
“…A prior study by Almishaal of 939 patients showed a statistically significant increase in subjective, self-reported incidence of audiovestibular symptoms in patients with COVID-19, but did not demonstrate significant differences between viral variants ( 15 ). However, it is difficult to assess the clinical significance of subjective, self-reported findings.…”
Section: Discussionmentioning
confidence: 77%
“…Auditory symptoms were reported to inflict approximately 24% of COVID-19 patients, with aural fullness as the chief complaint, followed by tinnitus and hearing loss 17. In contrast, vestibular symptoms were reported in approximately 35% of COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, detailed investigations, including imaging, are pertinent so as to avoid other causes of acute onset of hearing loss and vertigo, such as stroke or bleeding and intracranial tumour 19. Nevertheless, with the shift of variants causing COVID-19, reports on the rising number of patients presenting with audiovestibular symptoms have been demonstrated recently 17. Therefore, objective vestibular assessments are important to identify the affected vestibular end-organ, to monitor disease progression as well as treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Almishaal et al asociaron al mareo con el uso de medicamentos antirretrovirales y la hidroxicloroquina por su acción ototóxica (46). Por otro lado, Islamoglu et al, en su estudio de diplopía binocular horizontal, menciona que el paciente mejoró a los pocos días, indicando el tratamiento con hidroxicloroquina y azitromicina (47).…”
Section: Fuente: Elaborado Y Diseñada Por El Autorunclassified